SERAPAN TENAGA TENAGA KERJA PADA PERUSAHAN PERKEBUNAN KELAPA SAWIT DI DESA MANGKA KECAMATAN BAKAM KABUPATEN BANGKA - Santika, Fera; Setiawan, Iwan; Evahelda, Evahelda (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2020)
This study aims to describe the uptake of labor in oil palm plantation companies in Mangka Village, Bakam District, Bangka Regency, to analyze what factors influence the level of labor absorption in oil palm plantations in Mangka Village, Bakam District, Bangka Regency. This research was conducted in December 2018 until August 2019 in Mangka Village, Bakam District, Bangka Regency. The research method used was a survey method. The sampling method used was the quota sampling method with a sample of 76 people. Employment uptake in oil palm plantation companies was analyzed using descriptive statistics, while the factors affecting labor absorption were analyzed using multiple linear regression analysis. The results showed that the uptake of labor in oil palm plantation companies in Mangka Village, Bakam District, Bangka Regency over a period of 21 years had increased by 1%. Factors that influence the level of labor absorption in oil palm plantation companies are past labor absorption and education.